2006
DOI: 10.1063/1.2140682
|View full text |Cite
|
Sign up to set email alerts
|

Spheromak formation and sustainment studies at the sustained spheromak physics experiment using high-speed imaging and magnetic diagnostics

Abstract: A high-speed imaging system with shutter speeds as fast as 2 ns and double frame capability has been used to directly image the formation and evolution of the sustained spheromak physics experiment ͑SSPX͒ ͓E. B. Hooper et al., Nucl. Fusion 39, 863 ͑1999͔͒. Reproducible plasma features have been identified with this diagnostic and divided into three groups, according to the stage in the discharge at which they occur: ͑i͒ breakdown and ejection, ͑ii͒ sustainment, and ͑iii͒ decay. During the first stage, plasma d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 14 publications
3
10
0
Order By: Relevance
“…In the laboratory, jet propagation experiments have yielded direct information about how jets become collimated. Collimation near r = 0 is evident in Figure 2 showing simulations calibrated to measurements in the SSPX spheromak (Hooper et al 2012), corroborated by photographic studies of the early stages of jet formation in SSPX (Romero-Talams et al 2006). While for accretion disks we found that field lines emerge nearly vertically, the gun used in these experiments has an annular shape, causing some delay before field lines converge and straighten to form the equivalent of the central column in Figure 1.…”
Section: Evidence For the Model From Observations Experiments And Ssupporting
confidence: 74%
“…In the laboratory, jet propagation experiments have yielded direct information about how jets become collimated. Collimation near r = 0 is evident in Figure 2 showing simulations calibrated to measurements in the SSPX spheromak (Hooper et al 2012), corroborated by photographic studies of the early stages of jet formation in SSPX (Romero-Talams et al 2006). While for accretion disks we found that field lines emerge nearly vertically, the gun used in these experiments has an annular shape, causing some delay before field lines converge and straighten to form the equivalent of the central column in Figure 1.…”
Section: Evidence For the Model From Observations Experiments And Ssupporting
confidence: 74%
“…A flux rope model initially proposed to explain the amount of helicity needed for the closing of flux surfaces shortly after plasma breakdown in SSPX [5], is extended here to include the stepwise flux buildup seen during runs with multi-pulse gun current waveforms.…”
Section: The Flux Rope Modelmentioning
confidence: 99%
“…This process had been described previously in Refs. [5,12] from findings using only high-speed images and edge magnetics.…”
Section: A Initial Plasma Ejection From the Gun And Spheromak Formationmentioning
confidence: 99%
“…Rotation at the formation phase may also be present (see Refs. [12,13] and references therein), but our model cannot be applied to this case because of a short connection length during the formation phase. We also note that in the NIMROD simulations [9], a slow rotation of the modes was observed when two-fluid effects were included.…”
Section: The Modelmentioning
confidence: 99%